ANALYSIS’ PROCESSING OF DIGITAL IMAGE FOR DETECTING FACE PHOTO BY METHODE HAARCASCADE - Ahmad Fauzi (JOSAR (Journal of Students Academic Research), 2018)
Along with the development of this era, in the computerization’s era is so rapidly, there are many things or areas of life which grow up as well,both the area of technology and information. In the online admission, is needed to upload a photo of prospective students. To preventan uploading which not corresponding with context and suitability of image resolution which uploaded, that’s why, it’s needed to detect a face for making face photo of prospective students whois really quality. Face detection on digital image which is doneby methode of haarcascade,which is able to detect area of face on the picture to get a result. The result of trial produces the size of cropping of faceonthe picture is many defferences which corresponding with a picture which has tried.The writter is interested in making an aplication program by programming C++ dengan judul” ANALYSIS’ PROCESSING OF CITRA DIGITAL FOR DETECTING FACE PHOTO BY METHODE HAARCASCADE” This aplication can be expected which implemented in Admission of new students) Unisba Balitar.